Psychological Factors and Their Association with Ideal Cardiovascular Health Among Women and Men - Mathews, Lena (J Womens Health (Larchmt), 2018)
Background: The cardiovascular effects of stress and other psychological factors may be different between women and men. We assessed whether self-perceived adverse psychological factors were associated with achievement of ideal cardiovascular health (CVH) as measured by the American Heart Association's Life's Simple Seven (LS7) and whether this differed by sex. Methods: This was a cross-sectional study of employees from a large healthcare organization. The LS7 metrics (smoking, physical activity, diet, body mass index, blood pressure, cholesterol, and glucose) were each scored as ideal (2), intermediate (1), or poor (0). Total scores were categorized as optimal (11–14), average (9–10), and inadequate (0–8). Using logistic regression, we tested whether psychological factors obtained by questionnaire (self-perceived stress, low life satisfaction, hopelessness, sadness, depression, and anxiety) were associated with CVH, after adjustment for age, ethnicity, and education. Results: Among 9,056 participants, the mean (SD) age was 43 (12) years, 74% were women, 57% Hispanic/Latino, 17% white, and 16% black. Stress was associated with reduced odds of having optimal/average CVH [OR 0.58 (95% CI 0.50–0.66) and 0.63 (0.50–0.81), for women and men, respectively]. Similarly, depression was associated with reduced odds of optimal/average CVH [0.58 (0.43–0.78) and 0.44 (0.26–0.76), for women and men, respectively]. Low life satisfaction, hopelessness, sadness, and anxiety were also associated with statistically significantly lower odds of optimal/average CVH in women, but not in men; however, there were no interactions by sex. Conclusions: In an ethnically diverse population, both women and men with several adverse self-perceived psychological factors were less likely to have optimal or adequate CVH. Future studies are needed to determine whether addressing psychological stressors can improve CVH.